Community Service Activities: Express Your Imagination with Canva - Sibarani, Alexander.J.P; Hirzi, M Fakhurl; Pasaribu, Sutrisno Arianto; Siregar, Niki Yulia Sari; Halawa, Jerisekiawan (Jurnal Pengabdian Pancasila (JPP), 2024)
This community service program was held at Mayjend Sutoyo Vocational High School Medan with the theme “Express Your Imagination with Canva”. This activity aims to improve students' skills in graphic design using Canva as a tool to support creativity and digital marketing capabilities. The training involved lectures, discussions, and hands-on practice, focused on grade XII students. The results of the activity showed a positive response from participants, as well as a significant improvement in design skills. The program is expected to have a long-term impact in preparing students to enter the workforce with relevant digital skills.